In memoriam: Marco Avellaneda (1955–2022). (10th January 2023) - Cont, Rama
Abstract: Marco Avellaneda (1955–2022) was a leading figure in the development of mathematical modeling in finance and its dissemination among market practitioners. We provide a sketch of his trajectory and outline some of his main research contributions to mathematical finance.